(untitled) (Journal of International Studies, 2022)
The endless struggle between two seemingly incompatible but occasionally convergent concepts, namely liberal values and national interests, has determined United States (US) foreign policy and its implementation throughout the nation’s history. Based on the neoclassical realist assumptions shored up by the methodological insights offered by the five-dimensional pre-theory of foreign policy, this article reveals a persistent dichotomy in US foreign policy through the analysis of Washington’s response to the Arab Spring uprisings in Egypt, Libya, and Syria. Throughout history, US foreign policy has had a pendular behavioral pattern, swinging across a policy spectrum ranging from moralpolitik to realpolitik. While the inherent values-interests dilemma lies at the root of the inveterate oscillation of US foreign policy, the interplay of international stimulus and societal factors stands out as the principal source of its ambivalence, if not inconsistency, in the face of the upheavals that swept across the Middle East.